Girona: A Medieval City and the Modern Man, the Meeting - I. A. Malkovskaya (Ибероамериканские тетради)
Girona is a Spanish city that has a long history. Its medieval spirit allows people to immerse themselves in the past and restore historical memory. Girona is a heuristic model for reflecting on both medieval culture and the way a modern person identifies with it. Spain is a country that preserves its history through holiday celebrations (both on a local and regional scale), carnivals and folklore, yet at the same time it takes into account the interests of tourists from different countries by creating new ways of connecting with its heritage. One can make an exciting journey to the Hogwarts library, that is, to real medieval libraries, to the world of Game of Thrones characters. Girona has become a mysterious city of Braavos for fantasy fans. Popular culture combines fantasy and reality, mythology and history to meet the demand for medieval culture. Each person has the right to choose their identity. 20th century intellectuals set the trend for an identity search, with the most influential authors including the Annales school, J.R.R. Tolkien, «the father of fantasy», Mikhail Bakhtin who explored the carnival culture and Umberto Eco whose works are characterized by postmodern discourse. The past and a modern person as its protagonist meet each other in the 21st century, which manifests itself in videogames and live action games, carnivals, festivals and holidays. When it comes to discussing Spain’s historical heritage and drawing up itineraries to travel around the country, it is important to take into account the interests of new subcultures, tourists, participants of interactive events, cinephiles and those who simply admire the beauty of a medieval city. Girona invites one to contemplate the past that has already become relevant today.